REKAYASA PROSES BISNIS PADA E-COMMERCE B2B–B2C MENGGUNAKAN SISTEM AFILIASI - Febri Nova Lenti (JURNAL INFORMATIKA DAN KOMPUTER, 2017)
E-commerce B2B-B2C is a kind of E-commerce with forms of interaction Bussiness to Bussiness (B2B) and Bussiness to Customer (B2C) where there is interaction between producers (company, home industries, providers of goods and services) with distributors and retailers, which followed by distributors and retailers to consumers based on electronic media that is connected to the internet. The system is engineered using Affiliate System where the activity in these systems sell products or services of another person without having to buy or have products or services. The affiliate system uses a system of revenue sharing or commission in accordance with the agreement. How affiliate system can support B2B-B2C interactions as well as the application of information and communication technology appropriate to support business processes will be explorated in this research. Results to be obtained from this research is an E-commerce system that provides ease of process to support an information system of selling based on mobile and web from providers of goods and services to retailer and from the retailer to the consumer.Keywords:E -Commerce, Business Process, B2B, B2C, Afiliate, provider of goods, retailers, consumers